Exploring Conditions for Designing Citizen Observatories in Sri Lanka: The Case of Air Quality in Rural Areas - Chaminda Rathnayake; Somya Joshi; Teresa Cerratto-Pargman (Citizen Science: Theory and Practice)
Citizen observatories (COs) are socio-technical initiatives that seek to engage citizens interested in environmental issues via digital applications to gather ecological data, drawing on participatory approaches. While CO projects conducted in the Global North have successfully engaged citizens, less is known about how they engage with citizens in rural areas in the Global South. Herein, we address this knowledge gap by exploring conditions for designing COs in rural areas in Sri Lanka. We conducted a case study to examine how rural communities that reside close to industrial centers make sense of their surroundings, with a specific focus on air quality. With the aid of qualitative analysis of ten semi-structured interviews, we identify primary collective community practices that contribute to local air quality knowledge. The study contributes to discourses on conditions for designing COs by suggesting potential design features for community science participation and sense-making. Our findings indicate that most often, the citizen science practices identified and discussed by the literature on COs and human-computer interaction are at odds with rural communities’ priorities and sensing praxis in countries such as Sri Lanka. Thus, we argue for engaging with communities and their specific collective practices rather than with individuals to design COs in rural areas in Sri Lanka and in similar contexts. To give socio-technical initiatives such as COs a chance outside of the Global North, attention must be paid to how citizens experience, sense, and make sense of the local environment as part of a collective effort.